Endophytic fungi of leaf of Atlas pistachio of Dayate Aiat (Laghouat, Algeria) - Zareb A.; Smail-Saadoun N.; Rezki-Sekhi L. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Atlas Pistachio, Pistacia atlantica Desf. is an Anacardiaceae, ubiquitous North Africa and the Middle East. In Algeria, this species is widespread in arid regions where difficult natural conditions the push to form symbioses to counter the water deficit. Its leaves are deciduous. They are present on the tree when the rains decrease and temperatures rise. To mitigate its constraints symbiotic associations with mutualistic fungal endophytes are possible. Our sampling was done at a daya of the wilaya of Laghouat. Harvested in April 2013 and ten normal individuals subjectively selected leaves are stained by the method of Hayman and Phillips (1970) and observed under an optical microscope. Observations have shown the presence of several differently colored structures. Different ranges of colors are distinct along the limbus at all compartments of the leaflets. Endophytic fungi are noted in stomata, glandular hairs and between certain epidermal cells within parenchymal cells, but also in the primary and secondary veins (xylem and phloem). A variety of fungal endophytes is noted in the leaves of pistachio Atlas. These are probably able to maintain the eco-physiological and adaptive balance of this species under the restrictive conditions of the natural environment in which it lives.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)